Ruminal degradation of fibrous components of various feeds in cattle and buffalo - BHATIA, S K; SANGWAN, D C; PRADHAN, K; SINGH, SADHANA; SAGAR, VIDYA (The Indian Journal of Animal Sciences, 2013)
The relative disappearanccs and rates of degradation of DM. NDF and ADF for 10 nutritively variable feeds (2 to 16% Cp) were determined by simultaneously suspending the substrate in the rumen of caule and buffaloes. The overall average effective degradability did not differ between these ruminant species. However. some feed fibrous components exhibited differential disappearances due to cattle and buffaloes. The degradation of NDF and ADF in wheat straw-groundnut cake besides NDF from oat hay exceeded in buffaloes than in cattle, while the enhanced degradation of NDF fraction from wheat straw, paddy straw, pearimillel stover and berseem hay by cattle relative to buffaloes conformed to their dry matter degradabilities. The in sacco effective dcgradability and the rates of degradtion of test substrates appeared ID be influenced by the composition of feed dry matter. The dry matter fractional disappearance rate (hr1) varied from 0.0053 to 0.0473 in cattle and 0.0150 to 0.0747 in buffaloes. The highest DM degradation rate in berseem hay was about 2-fold in buffaloes vis-a-vis Cattle. The NDF degradation rate in cattle and buffaloes ranged from 0.0068 10 0.0378/hr and 0.0108 to 0.491/hr respectively. Fractional degradation rate (hr1) of ADF fell between 0.0063 and 0.0461 in cattle and 0.0057 and 0.0461 in buffaloes. The average degradation rate for DM (0.0245 vs0.0373/hr). NDF (0.0224 vs 0.0317/hr) and ADF (0.0233 vs O.0275/hr) Cor the two respective ruminant species may indIcate a slightly better degradation in buffaloes relative to cattle. Such phenomenal variationmay sequentially govern the romen fill of these ruminant species. Further, data inferred that the rate of degradation of NDF and ADF tended 10 be closer to those of dry matter.